2015
DOI: 10.3171/2014.10.jns1460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracranial pressure monitoring on mortality in patients with traumatic brain injury: a systematic review and meta-analysis

Abstract: T raumaTic brain injury (TBI) is a common cause of death and disability worldwide. 17 Despite some claims to the contrary, no clear decrease in severe TBI-related mortality or improvement in overall outcome has been observed over the past 2 decades. 24 Recently, many studies have shown that the presence and frequency of high intracranial pressure (ICP) are predictive of the outcome of severe TBI. 18,23 Thus, ICP monitoring has been widely used in the management of severe TBI. Indeed, the Brain Trauma Foundatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 35 publications
0
64
1
1
Order By: Relevance
“…Several studies evaluating the impact of ICP monitoring on the outcomes of sTBI have yielded varying results [7-16]. The BEST-TRIP trial was published in 2012 and was based on cases in several ICUs in South America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluating the impact of ICP monitoring on the outcomes of sTBI have yielded varying results [7-16]. The BEST-TRIP trial was published in 2012 and was based on cases in several ICUs in South America.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial pressure (ICP) monitoring is a key component of the guidelines, and management recommendations in each subsequent update are tailored towards treating intracranial hypertension (ICH) [2, 3]. Although this has biologic plausibility, the results of various studies examining the impact of ICP monitoring on the outcomes of sTBI patients have been conflicting [7-16]. It is also plausible that early identification of elevated ICP and management of ICH would improve outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most published observational studies did not support the use of ICP monitoring in patients with severe TIB. Su et al performed a meta-analysis of patients with TBI and implied that no benefit was achieved in patients who underwent ICP monitoring [43], and Yuan implicated that ICP monitoring did not contribute to lower mortality rates in patients with severe TBI [44]. However, the results of the above meta-analyses did not conform to the theoretical expectations of ICP monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown variable levels for management of neuronal trauma. Our survey shows that the EVD is the preferred technique for ICP monitoring in patients with traumatic brain injury (16)(17)(18)(19)(20)(21). We found that using techniques such as Ghajar Guide is infrequent, perhaps because of the high cost of this system in a country with limited resources such as Colombia.…”
Section: Discussionmentioning
confidence: 90%